PROMOSI PERPUSTAKAAN MELALUI MEDIA SOSIAL INSTAGRAM DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN LIMA PULUH KOTA - Yovita Melamanda; Yona Primadesi (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
This research is motivated by the impact of increasingly rapid technological developments, so that it affects the existence of libraries and archives in 50 Kota. The purpose of this study was to describe the context, content, communication, and connection of Instagram at the Library and Archives Service of 50 Kota Regency as a promotional media. This is a qualitative study that uses the descriptive method. Interviewing, observation, and documenting procedures are used to obtain data. Based on research findings and discussion, it shows that library promotion through social media Instagram has fulfilled two of the four elements used. The elements that are met are the application of communication and connection. Based on the research results the application of context or message content seen from the clarity and completeness of the message is not yet persuasive. The application of content or message packaging has not been running effectively, it can be seen from the uploaded content that is less varied and the appearance of the feed on the @perpustakaandaerah50k account is less attractive. The application of communication or interaction between the @perpustakaandaerah50k admin and followers has been going well, as can be seen from the comments and direct messages which were responded positively by the admin. And the application of the connection is also going well, as can be seen from the use of the hashtag feature in promotions through Instagram social media, making it easier for followers to get information.